RETRACTED: CRISPR/Cas9-Mediated OC-2 Editing Inhibits the Tumor Growth and Angiogenesis of Ovarian Cancer - Lu, Tongyi; Zhang, Ligang; Zhu, Wenhui; Zhang, Yinmei; Zhang, Simin; Wu, Binhua; Deng, Ning (Frontiers in Oncology, 2020)
Ovarian cancer is the leading cancer-related causes of death in women worldwide. It is of great relevance to understand the mechanism responsible for tumor progression and identify unique oncogenesis markers for a higher chance of preventing this malignant disease. The high-expression OC-2 gene has been shown to be a potential candidate for regulating oncogenesis and angiogenesis in ovarian cancer. Hence, we wished to investigate the impact of OC-2 gene on ovarian cancer aggressiveness. CRISPR/Cas9, a gene editing tool, allows for direct ablation of OC-2 at the genomic level and we successfully generated OC-2 KO cell lines from SKOV3 and CAOV3 cells. In apoptosis assay, OC-2 KO induced the apoptosis activation of tumor cells, with the up-regulation of Bax/Caspase-8 and the down-regulation of Bcl-2. Consequently, the proliferation, migration and invasion of OC-2 KO cell lines were significantly inhibited. Assays of qRT-PCR and Western blotting showed that the expression levels of pro-angiogenic growth factors VEGFA, FGF2, HGF and HIF-1α and the activation of Akt/ERK pathways were significantly down-regulated at the loss of OC-2. In xenograft model, OC-2 KO potently suppressed the subcutaneous tumor growth, with the inhibition exceeded 56%. The down-regulation of CD31 and relevant pro-angiogenic growth factors were observed in OC-2 KO tumor tissues. Taken together, OC-2 depletion negatively regulated the ovarian cancer progression possibly by apoptpsis activation and angiogenesis inhibition. This work revealed a pivotal regulator of apoptpsis and angiogenesis networks in ovarian cancer, and we applied CRISPR/Cas9 system to transcription factor pathway for developing a broad-acting anti-tumor gene therapy.